Portrayal of negative qualities in a doctor as a potential teaching tool in medical ethics and humanism: Journey to the End of Night by Louis-Ferdinand Céline. Issue 964 (3rd February 2006) - Wolf, G
Abstract : Fictional stories about physicians and patients are increasingly used as a powerful teaching resource for medical students. Very often, but not exclusively, stories of physicians as positive role models are selected to teach students virtues and ethical values. Negative role models are rarely used and if so, physicians are rather described as medical quacks in such fiction then exhibiting primarily a corrupted character. I suggest that a fictional story that presents exclusively a negative role model of a physician could also be a valuable, admittedly difficult, teaching resource to demonstrate the consequences of absolute loss of ethical standards and virtues in physicians. A not widely known example of this genre is Louis-Ferdinand Céline's (1894–1961) novel Voyage au bout de la nuit ( Journey to the End of the Night ), published in 1932. Having a strong autobiographical background, the novel described the adventures of the medicine student, Ferdinand Bardamu, during the first world war, in the African colonies as a trader, in the United States of America as factory worker, and later after finishing his education, as a doctor for the poor. Unfortunately, Dr Bardamu develops an unprofessional, even criminal behaviour, and may serve as a negative role model for the virtues of physicians. This article will familiarise the reader with the novel and its physician author.